2006
DOI: 10.1097/01.mou.0000193377.14694.7f
|View full text |Cite
|
Sign up to set email alerts
|

Training in laparoscopic urology

Abstract: In spite of the abundant literature there is still little evidence about the learning mechanism involved in acquiring laparoscopic skills. Physical and virtual reality simulators have been proven to be efficient in improving dexterity and some evidence exists of a positive transfer from virtual reality to the operating room in cholecystectomy. Very few models, however, have been described for reconstructive urology, and effective transfer to the operating room has not yet been proven, although validation work … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 29 publications
0
19
0
Order By: Relevance
“…2,4,5,7,8,[10][11][12][14][15][16][22][23][24] Unfortunately, financial, technical, and operational obstacles more often limit their application. Thus, anatomical models built from a myriad of materials 2,14,16,24 and using computational and artistic techniques 12 have become an interesting option in simulating endoscopic procedures with good accuracy at reasonable costs.…”
mentioning
confidence: 99%
“…2,4,5,7,8,[10][11][12][14][15][16][22][23][24] Unfortunately, financial, technical, and operational obstacles more often limit their application. Thus, anatomical models built from a myriad of materials 2,14,16,24 and using computational and artistic techniques 12 have become an interesting option in simulating endoscopic procedures with good accuracy at reasonable costs.…”
mentioning
confidence: 99%
“…However, at first difficulties needed to be overcome in the surgical environment, such as hand-eye coordination, depth perception, and endoscopic suturing. This was accomplished by training, which incorporated different systems and methods, such as video box trainers, animal and human cadaver models, and more recently, virtual simulators [4]. The advent of laparoscopy thus focused attention on the concept of "learning curves."…”
Section: Learning Laparoscopymentioning
confidence: 99%
“…In 1976, Cortesi et al [1] performed the first urologic laparoscopic procedure to treat cryptorchid testes, but the real laparoscopic wave in urology was marked by Clayman's first laparoscopic nephrectomy in 1991 [2] and Vallancien and Guillonneau's first laparoscopic prostatectomy with refined technique in 1998] [3]. Urology has traditionally been a technologically bounded field, but it embraced laparoscopy and reproduced open standards in the endoscopic environment, including useful variations in terms of approach (transperitoneal, extraperitoneal, and hand-assisted) [4].…”
Section: Historical Development Of Urologic Laparoscopymentioning
confidence: 99%
“…While simple simulators are sufficient for the development of basic skills, virtual reality simulators can be more effective in the acquistion of complex skills. [6,7] Laparoscopy training boxes are cheap and provide the facility of simulation for several skills. The training box, which was once developed at home with a laptop, a simple web camera, a cardboard box and a table lamp, is now produced commercially and studies have shown that it provides the possibility of laparoscopic training in the same way as a video pelvitrainer.…”
Section: Dry Laboratory Training With Pelvitrainermentioning
confidence: 99%